Preliminary design of potential storage facility for low and intermediate level radioactive waste (Rudarsko-geološko-naftni zbornik, 2018)
An issue concerning the management of radioactive waste (RAW) in the Republic of Croatia continuously rises due to the lack of systematic solutions. In this paper emphasis is being placed on the storage of RAW, as one of the important phases of RAW management. The current RAW storage facilities are not sufficient and there is a need for a new facility for low and intermediate level radioactive waste (LILW), since such waste accounts for the largest part of RAW. For this reason a preliminary estimate for a one-storey structure was carried out, a potential storage facility of LILW that would be constructed at the location of Čerkezovac, Trgovska Gora, the Republic of Croatia, as the currently most prominent location for the realization of the RAW storage facility. The geological characteristics of the site were analysed and, in accordance with the relevant regulations, a static design of the facility was made in the ETABS and SAFE program packages. The construction is typical reinforced concrete structure, rectangular in plan (10,0 x 30,0 m) with a height of 5,9 m. The selected location meets the given parameters of geological characteristics, while the construction meets the given load and serviceability conditions. However, a more detailed analysis would be necessary if the decision to construct such storage facility would be made.